Numerical computation in science and engineering - Pozrikidis, C. (Topics in Chemical Engineering, 2008)
Designed for non-expert student, enthusiast, or researcher, this two-volume text provides an accessible introduction to numerical computation and its applications in science and engineering. It assumes no prior knowledge beyond undergraduate calculus and elementary computer programming. Fundamental and practical issues are discussed in a unified manner with a generous, but not excessive, dose of numerical analysis. Topics are introduced on a need to know basis toconcisely illustrate the practical implementation of a variety of algorithms and demystify seemingly esoteric numerical methods. Algorithms that can be explained without too much elaboration and can be implemented within a few dozen lines of computer code are discussed in detail, and computer programsin Fortran, C++, and Matlab are provided. Algorithms whose underlying theories require long, elaborate explanations are discussed at the level of first principles, and references for further information are given. The book uses numerous schematic illustrations to demonstrate concepts and facilitate their understanding by providing readers with a helpful interplay between ideas and visual images. Real-world examples drawn from various branches of science and engineering are presented. Updatedinformation on computer technology and numerical methods is included, many new and some original topics are introduced. Additional solved and unsolved problems are included.